Using a Functional Upper Limb Motor Task to Predict Cognitive and Functional Decline in Mild Cognitive Impairment and Alzheimer's Disease. - Koppelmans, Vincent; Duff, Kevin; Schaefer, Sydney Y. (Neurorehabilitation & Neural Repair, 2025)
Background: Predicting the rate of cognitive and functional decline over the course of Mild Cognitive Impairment (MCI) and Alzheimer's disease (AD) is vital for advancing clinical care and research initiatives. Objectives: The current study examined if a functional upper limb motor task could predict 1-year change in cognition (Mini Mental Status Examination [MMSE]) and daily function (Quick Dementia Rating System [QDRS]) from a sample of 61 cognitively intact, 35 MCI, and 32 AD subjects. Results: Analyses adjusted for age, sex, and education showed that performance speed and variability on the motor task significantly predicted change in performance on the MMSE and QDRS over 1 year, and that these effects were small to medium in size (η2 = 0.04-0.05). Conclusion: These results suggest the potential of a simple motor task to estimate disease progression in MCI and AD, which could be used to provide additional clinical resources for and enrich clinical trials with those most likely to decline.